Sources of Dietary Fiber Affect the SCFA Production and Absorption in the Hindgut of Growing Pigs - Bai, Yu; Zhou, Xingjian; Zhao, Jinbiao; Wang, Zhenyu; Ye, Hao; Pi, Yu; Che, Dongsheng; Han, Dandan; Zhang, Shuai; Wang, Junjun (Frontiers in Nutrition, 2022)
Different sources of dietary fiber (DF) on short-chain fatty acids (SCFA) production and absorption in the hindgut of growing pigs were studied by an in vivo-vitro (ileal cannulated pigs and fecal inoculum-based fermentation) method. Thirty-six cannulated pigs (body weight: 48.5 ± 2.1 kg) were allocated to 6 treatments with the same DF content (16.5%) randomly, containing wheat bran (WB), corn bran (CB), sugar beet pulp (SBP), oat bran (OB), soybean hulls (SH) and rice bran (RB) respectively as DF sources. Pigs were allowed a 15-day for diet adaptation, and then fresh ileal digesta and feces were collected to determine SCFA concentration which was normalized for food dry matter intake (DMI) and the hindgut DF fermentability. Fecal microbiota was inoculated into the freeze-dried ileal digesta samples to fermentation in vitro, to predict the ability of SCFA production and absorption in the hindgut. SH group generated the largest amount of total SCFA and propionate in ileal digesta and fecal samples of growing pigs (P < 0.05). Nonetheless, the predicted acetate, total SCFA production and absorption in the SBP group were the highest (P < 0.01), but the lowest in the OB group (P < 0.01) among all groups, even SBP and OB group had a similar ratio of soluble DF (SDF) to insoluble DF (IDF). The CB group with high determined ileal and fecal butyrate concentration had the lowest amount of butyrate production and absorption in the hindgut (P < 0.01). Overall, the source of DF has a great impact on the production and absorption of SCFA in the hindgut, and SBP fiber had a great potential to produce SCFA during fermentation.